PENGARUH MODEL DISCOVERY LEARNING BERBANTUAN MEDIA WORDWALL TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN PANCASILA DISEKOLAH DASAR - Aziyatun Adinda Fitria; Dayu Rika Perdana; Roy Kembar Habibi; Fadhilah Khairani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the low learning outcomes of fifth-grade students in the Pancasila Education subject at SD Negeri 11 Metro Pusat, which resulted from the use of less varied instructional models and the limited application of interactive learning media. This research aims to determine the effect of the Discovery Learning model assisted by Wordwall media on students’ learning outcomes. The study employed a quantitative approach with a quasi-experimental method using a Nonequivalent Control Group Design, involving all 66 fifth-grade students as the sample through a saturated sampling technique. Data were collected using tests (pretest and posttest) to measure learning outcomes, as well as non-test techniques, including observations (observation sheets) and documentation, to examine students’ learning activities. Data analysis included normality testing, homogeneity testing, and simple linear regression. The results indicate that the Discovery Learning model, assisted by Wordwall media, significantly improves students’ learning outcomes, as evidenced by the higher post-test scores in the experimental class compared to the control class, with a statistical significance value of 0.00 < 0.05. Therefore, the Discovery Learning model, assisted by Wordwall media, has been proven effective in enhancing learning outcomes in Pancasila Education at the elementary school level.